Brugada-like electrocardiographic changes induced by fever. Issue 1 (20th December 2006) - Unlu, M; Bengi, F; Amasyali, B; Kose, S
Abstract : As "time is myocardium" in the settings of acute myocardial infarction, it is important to make the diagnosis as quickly as possible, and a high clinical suspicion is needed to avoid missing the diagnosis, resulting in unwarranted interventions. The electrocardiogram is a crucial tool in the identification of acute chest pain, enabling a detailed analysis of patterns of ST-segment elevation. We describe the case of a 22-year-old man who presented with fever, with dynamic electrocardiographic changes similar to the Brugada syndrome. These electrocardiographic anomalies disappeared when the temperature returned to normal.